Performance, carcass traits, and meat fatty acid profile and quality of Anglo-Nubian kids fed diets supplemented with vegetable oils - Toniolo Chavari, Andreia Cristina [UNESP]; Marques, Raquel Ornelas [UNESP]; Barros Gomes, Helen Fernanda; Lara Canizares, Gil Ignacio; Brito, Evelyn Prestes [UNESP]; Lourencon, Raquel Vasconcelos; Lima Meirelles, Paulo Roberto de [UNESP]; Goncalves, Heraldo Cesar [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2021)
The objective of this study was to evaluate the inclusion of vegetable oils in goat kid diets on performance, carcass traits, and meat composition, quality, and fatty acid profile. Forty-eight Anglo Nubian kids were evaluated in a completely randomized experimental design with four treatments, namely, control diet and diets including 2.5% canola, sunflower, or soybean oils. The animals were slaughtered at 30 kg live weight and performance, carcass and meat quality, centesimal composition, and fatty acid profile were evaluated. The treatments did not influence carcass yield or meat color. Among the saturated fatty acids, only caprylic, palmitic, and heptadecanoic acids differed among the treatments, whereas total saturated fatty acids decreased in the sunflower oil treatment. Monounsaturated fatty acids were not influenced by lipid supplementation. Among the polyunsaturated fatty acids (PUFA), linoleic acid was highest in the sunflower oil-treated group. Total PUFA were higher for the soybean oil-supplemented group, but similar to that achieved with sunflower oil. The highest omega-6 content was obtained with dietary inclusion of sunflower oil, whereas conjugated linoleic acid, atherogenicity index, and hypocholesterolemic:hypocholesterolemic ratio improved with the inclusion of sunflower and soybean oils. Supplementation with vegetable oils improves the fatty acid profile of kid meat without affecting animal performance. Better results are obtained with sunflower and soybean oils; therefore, it is up to the producer to choose the diet according to its cost.
Keywords: caprine; lipid supplementation; meat quality